EP926 PAD enzymes as a candidate therapeutic target in ovarian cancer. (1st November 2019) - O'Toole, S; Melarcode, H; Elbaruni, S; AbuSaadeh, F; Ward, M; Gallagher, M; Norris, L; Gray, S; O`Leary, J; Mohamed, B
Abstract : Introduction/Background: Ovarian cancer (OC) is the fifth most common cancer among Irish women with a higher incidence rate than other European countries. OC patients have a good response rate to first line chemotherapy treatment. However, the prognosis for OC following treatment is very poor in the majority of OC patients, especially patients with stage III or IV disease on diagnosis. Patients respond well initially to chemotherapy but go on to develop recurrent chemoresistant disease. Peptidyl arginine deiminase type 4 (PADI4) performs post-translational modification and catalyzes the arginine residue to a citrulline in numerous protein substrates. Citrullination of histones, cytokeratin, antithrombin and fibronectin have been confirmed to be involved in abnormal apoptosis, altered coagulation, and disordered cell proliferation, all of which are main features of primary tumors and metastasis. As PAD enzymes have been shown to be elevated in certain human diseases including autoimmune diseases and cancer, we hypothesized that targeting this enzyme with small molecule inhibitors such as GSK484 and GSK199 could lead to a novel therapeutic strategy. Therefore, we propose to investigate their therapeutic potential in a panel of OC cell lines and ex-vivo explants. Methodology: OC cell lines and ex-vivo explants were exposed to various concentrations of PADI4 inhibitors at different time points. PADI4 expression, cell cycle, viability, caspase 3 and 8 activation were measured using immunoblotting, immunohistochemistry and FACS analysis. Results: We demonstrated an inhibition of PADI4, changes in cell cycle status, reduction in cell viability and increased caspase 3, and 8. All these changes were concentration dependent. Conclusion: Our study observed the role of PADI4 in cell proliferation, apoptosis. These results suggests that PADI4 is involved in cell growth and death. GSK484 and GSK199 presents a promising direction in the search for novel OC treatment strategies. Disclosure: Nothing to disclose.